Assessing the Relationship between Serum Testosterone Levels and COVID-19 Outcomes in Admitted Patients - Abedi, Amir Reza; Dashti, Mohammad; Salehi Mashhadsari , Seyyed Pooria; Eghbaldoost, Amirreza; Mehravar, Roshanak; Ghadirzadeh, Erfan; Dashti, Reza; Allameh, Farzad (Archives of Men’s Health, 2023)
Introduction: With the emergence of the worldwide COVID-19 pandemic, a high toll of mortality and morbidity was imposed on Iran. Despite endeavors to control the disease using the social distancing protocols, isolations, quarantine and vaccination, COVID-19 is still afflicting individuals by mutation and development of new variants. Studies suggest higher morbidity and mortality among men compared to women, and in men with underlying diseases. Studies suggest low serum testosterone level as a risk factor for more severe diseases. We aimed to assess the relation of testosterone level with laboratory investigation and its effect on COVID-19 disease outcomes. Materials and Methods: Seventy patients were selected from those referred to Shohada-e-Tajrish hospital during February 2022 till July 2022. The patients were further categorized in two groups regarding their need for respiratory support: patients who did not need invasive respiratory support and patients who needed invasive respiratory support and were admitted to the intensive care unit. Blood samples were collected for laboratory examination. Each patient was followed for one month, and the outcomes were recorded. Results: The mean age of the participants was 64.44 years including 33 men and 37 women. Mean serum total and free testosterone level was 0.45 nmol/L and 1.22 nmol/L, respectively. Demised patients were significantly older and had significantly lower total testosterone levels. D-dimer was significantly higher in demised patients. Conclusion: Serum total testosterone levels can be used as a prognostic factor to predict COVID-19 patients’ prognosis. Serum total testosterone is inversely associated with disease severity, and lower serum total testosterone level is significantly associated with higher mortality. Moreover, inflammatory markers such as D-dimer can be used to determine prognosis and severity.